The Mediating Effect of Work Engagement on competence, work environment and job satisfaction - Pranitasari, Diah; -, Julian; Said, Meldasari; Nugroho, Sukmo Hadi (Jurnal Manajemen, 2022)
This study aims to determine the competence and work environment on job engagement and job satisfaction of employees for PT. Yamaha Music Manufacturing Indonesia. The sample in this study was 100 contract employees, using purposive sampling technique. The analysis used is SEM PLS research to test the Inner model, outer model and hypotheses. The results of the study stated: (1) Competence has an effect on work engagement by 55.2%. (2) The work environment has an effect on work engagement by 39.1%. (3) Competence has an effect on job satisfaction by 36.2%. (4) The work environment has an effect on job satisfaction by 35.2%. (5) Work engagement has no significant effect on job satisfaction. (6) Work engagement does not mediate competence in influencing job satisfaction. (7). Work engagement does not mediate the work environment in influencing job satisfaction.